(untitled) (Padmakanya Journal of Science and Technology, 2025)
Above Ground Tree Biomass (AGTB) and Soil Organic Carbon (SOC) in forests contribute significantly to improving soil health and mitigating climate change through long-term carbon sequestration. Quantities of carbon sequestered, however, vary among tree species compositions. Hence, this study assessed AGTB and SOC across three tree species stands-Alnus nepalensis, Pinus roxburghii, and Neolitsea cuipala-in the protected Gokarna Rajnikunj Forest of central Nepal. Results showed that Pinus stands had the highest AGTB (1,050.94 ± 522.95 t ha-1), while Alnus stands recorded the highest SOC stock (248.97 ± 70.20 t ha-1), despite having comparatively lower biomass. Soil properties, particularly pH and moisture content, varied significantly among species and influenced SOC accumulation. Notably, SOC levels in this forest exceeded those reported in comparable ecosystems. These findings highlight the importance of species-specific forest management strategies and support the integration of soil carbon considerations into broader conservation and climate policy frameworks to maximize carbon sequestration, biodiversity, and ecosystem resilience.